Disenfranchised Guilt—Pet Owners’ Burden - Lori R. Kogan; Cori Bussolari; Jennifer Currin-McCulloch; Wendy Packman; Phyllis Erdman (Animals, 2022)
Guilt refers to an unpleasant emotional state associated with one’s behaviors, thoughts, or intentions, and it is based on the possibility that one may be in the wrong or that others may have this perception. Parental guilt is one common subtype and is often associated with work–family conflict (WFC). WFC and related guilt have been found to be associated with depression and anxiety. Through an online anonymous survey, the current study was designed to explore dog owners’ guilt surrounding their dogs. Results suggest that dog owners’ guilt and WFC associated with their dog are at levels similar to those reported in human family studies. Additionally, the relationship between dog owners’ guilt and discrepancy between participants’ actual and ideal self, in regard to the role of a dog owner, also mirrored human-only family research. Because pet-related guilt is unrecognized, acknowledged, or supported, we suggest it is disenfranchised. As people return to work, in this period of post-COVID-19 pandemic time, it is paramount that companies and communities acknowledge pet owner guilt and WFC and help owners find practical, effective solutions.